Unexpected hematologic malignancies after prostatectomy: Case report and literature review. Issue 4 (November 2021) - Karademir, Barış; Kısa, Erdem; Özbilen, Mert Hamza; Bildirici, Çağdaş; Karabacakoğlu, Burak; Süelözgen, Tufan; İlbey, Yusuf Özlem; Küçük, Ülkü; Olgun, Aybüke
Introduction: Voiding symptoms, storage symptoms and post-voiding symptoms together constitute lower urinary tract symptoms (LUTS). Chronic lymphocytic leukemia (CLL) is the most common leukemia in adults. The most common finding is lymphadenomegaly. Although infrequent, extranodal sites of involvement such as prostate can be detected. Mantle cell lymphoma (MCL) is a subtype of B cell non-Hodgkin lymphomas. Extranodal involvement findings such as prostate may be observed. In this case report, we will present a case in which we performed an open suprapubic prostatectomy (Freyer's) and had CLL as a result of pathology, and a case whose pathology was MCL after transurethral resection of the prostate. Case 1: A 60-year-old male patient with LUTS for 6 years. Open suprapubic prostatectomy (Freyer's) was performed on the patient. The pathology result of the prostatectomy material was compatible with CLL involvement. Case 2: A 62-year-old male patient with LUTS for 4 years. Transurethral resection of the prostate (TUR-P) was performed on the patient. The pathology result of the prostate was compatible with MCL involvement. Discussion and Conclusion: There are limited number of cases have been reported about CLL pathology after prostatectomy due to benign prostatic obstruction (BPO). There is no study indicating how often CLL pathology is seen after open prostatectomy or TUR-P due to BPO. In patients with CLL pathology after RRP, open prostatectomy, TUR-P, the need for additional surgery, the difference in prognosis or the difference between the treatment have not been shown in the studies. It should be kept in mind that patients with leukocytosis, lymphocytosis, cytopenias, and LUTS in their clinical presentation and who have not yet been diagnosed with CLL and other hematological malignancies such as mantle cell lymphoma may also have prostate gland involvement and can be diagnosed incidentally by any prostatic intervention.